How Tillage and Crop Rotation Change the Distribution Pattern of Fungi - Orrù, Luigi; Canfora, Loredana; Trinchera, Alessandra; Migliore, Melania; Pennelli, Bruno; Marcucci, Andrea; Farina, Roberta; Pinzari, Flavia (Frontiers in Microbiology, 2021)
Massive sequencing of fungal communities showed that climatic factors, followed by edaphic and spatial variables, are feasible predictors of fungal richness and community composition. This study, based on a long-term field experiment with tillage and no-tillage management since 1995 and with a crop rotation introduced in 2009, confirmed that tillage practices shape soil properties and impact soil fungal communities. Results highlighted higher biodiversity of saprotrophic fungi in soil sites with low disturbance and an inverse correlation between the biodiversity of ectomycorrhizal and saprotrophic fungi. We speculated how their mutual exclusion could be due to a substrate‐mediated niche partitioning or by space segregation. Moreover, where the soil was ploughed, the species were evenly distributed. There was higher spatial variability in the absence of ploughing, with fungal taxa distributed according to a small-scale pattern, corresponding to micro-niches that probably remained undisturbed and heterogeneously distributed. Many differentially represented OTUs in all the conditions investigated were unidentified species or OTUs matching at high taxa level (i.e. phylum, class, order). Among the fungi with key roles in all the investigated conditions, there were several yeast species known to have pronounced endemism in soil and are also largely unidentified. In addition to yeasts, other fungal species emerged as either indicator of a kind of management or as strongly associated with a specific condition. Plant residues played a substantial role in defining the assortment of species.